Persepsi Masyarakat Tentang Kinerja Kantor Search and Rescue Medan dalam Pencarian Orang Hilang di Gunung Sibayak - Hisar Turnip; Yan Hendra; Armansyah Matondang (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2020)
This research tries to examine how the perception of society that is formed on local community which located at SAR Medan operation conducted search operation of missing person in Sibayak Mountain. The theory used in this research is the theory of perception, Society and Performance. The method used in this research is qualitative method in the form of descriptive study.  Data analysis that researchers use is data analysis made by Miles and Huberman. Research subjects in this study involving 3 local people who are in the area they were selected using sampling snowball techniques treated through interviews. Based on the research results obtained conclusion stating that the public perception about the performance of SAR Medan was not good or tend to negative,